CHEMICAL BASIS FOR THE ANTIMICROBIAL ACTIVITY OF ACETANILIDES - Bravo,Hector R. (Sociedad Chilena de Química, 2003)
In vitro antimicrobial activity of a series of substituted acetanilides against S. aureus, E. coli and C. albicans were measured at two concentrations, 250 mug/ml and 500 mug/ml. Only the structures substituted with halogens in Calpha and electron acceptors in the aromatic ring are bioactive. The results are rationalized in terms of the acid properties of the N-H bond, as calculated using AM1-MO theory